2020
DOI: 10.21203/rs.3.rs-34275/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characterisation and the improved molecular diagnosis of autosomal dominant cone-rod dystrophy in patients with SCA7

Abstract: Purpose To evaluate the retinal phenotype and genetic features of Chinese patients with spinocerebellar ataxia type 7 (SCA7). Methods Detailed ophthalmic examinations, including electroretinograms, fundus photography, fundus autofluorescence and optical coherence tomography, were performed to analyse the retinal lesions of patients with SCA7. A molecular genetic analysis was completed to confirm the number of CAG repeats in ATXN7 gene on the patients and their family members. Results Eight patients from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Abe et al also utilized 633-nm SLO imaging and demonstrated a granular aspect of the posterior pole in five of the six patients they examined [14]. Loss of the ellipsoid layer, RPE changes, and decreased central retinal thickness have been reported numerous times [13,15,17,18,21,28,31,32], indicating how the central cones become affected at an early stage of the disease. In a case series including seven patients, Manrique et al investigated the RNFL peripapillary thickness and revealed reduced thickness in all their patients, with common sparing of the temporal peripapillary quadrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abe et al also utilized 633-nm SLO imaging and demonstrated a granular aspect of the posterior pole in five of the six patients they examined [14]. Loss of the ellipsoid layer, RPE changes, and decreased central retinal thickness have been reported numerous times [13,15,17,18,21,28,31,32], indicating how the central cones become affected at an early stage of the disease. In a case series including seven patients, Manrique et al investigated the RNFL peripapillary thickness and revealed reduced thickness in all their patients, with common sparing of the temporal peripapillary quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…Katagiri et al recorded preserved rod responses in one patient [18]; Miller et al performed full-field ERG on four patients who had affected cone responses, while only one patient showed a combination of cone and rod degeneration [19]. On other occasions, the scotopic response decreased to some degree or as much as the photopic response, suggestive of cone-rod dystrophy [11,19,22,25,27,30,31]. Multifocal ERG (mfERG), evaluating the cone function in localized areas of the macular region, recorded significantly reduced amplitudes within the foveal area; in more advanced patients, amplitudes were reduced even in the outer mfERG areas [17].…”
Section: Discussionmentioning
confidence: 99%